2006
DOI: 10.1210/me.2005-0525
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Functional Estrogen Receptors at the Plasma Membrane

Abstract: Although rapid signaling by estrogen at the plasma membrane is established, it is controversial as to the nature of the receptor protein. Estrogen may bind membrane proteins comparable to classical nuclear estrogen receptors (ERs), but some studies identify nonclassical receptors, such as G protein-coupled receptor (GPR)30. We took several approaches to define membrane-localized estrogen-binding proteins. In endothelial cells (ECs) from ERalpha/ERbeta combined-deleted mice, estradiol (E2) failed to specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
370
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 478 publications
(398 citation statements)
references
References 43 publications
15
370
2
11
Order By: Relevance
“…However, it is now widely accepted that some of the actions of estrogen are quite rapid and cannot be attributed to the classical nuclear-initiated steroid signaling of ERα or ERβ. One view is that both nuclear and plasma membrane-associated ERs might be products of the same genes (Razandi et al, 1999, Boulware et al, 2005, Pedram et al, 2006, Szegõ et al, 2006, Dewing et al, 2007. This belief stems primarily from the fact that many of the rapid effects of E2 can be induced by selective ERα or ERβ ligands, antagonized by the ER antagonist, ICI 182,780, or are lost in animals bearing mutations in ERα and/or ERβ genes (Couse and Korach, 1999, Singer et al, 1999, Dubal et al, 2001, Wade et al, 2001, Abraham et al, 2003, Boulware et al, 2005.…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…However, it is now widely accepted that some of the actions of estrogen are quite rapid and cannot be attributed to the classical nuclear-initiated steroid signaling of ERα or ERβ. One view is that both nuclear and plasma membrane-associated ERs might be products of the same genes (Razandi et al, 1999, Boulware et al, 2005, Pedram et al, 2006, Szegõ et al, 2006, Dewing et al, 2007. This belief stems primarily from the fact that many of the rapid effects of E2 can be induced by selective ERα or ERβ ligands, antagonized by the ER antagonist, ICI 182,780, or are lost in animals bearing mutations in ERα and/or ERβ genes (Couse and Korach, 1999, Singer et al, 1999, Dubal et al, 2001, Wade et al, 2001, Abraham et al, 2003, Boulware et al, 2005.…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…This finding does not mean that ERα is sequestered within the nucleus since it has been shown to undergo a dynamic intracellular shuttling (Maruvada et al, 2003;Nonclercq et al, 2007;Stenoien et al, 2000) which seems to determine the type of response to estrogen signaling (Leclercq et al, 2006 (Acconcia, Kumar, 2006;Pedram et al, 2006;Song, 2007). In contrast, nuclear form(s) of ERα directly regulate gene expression (Nuclear Initiated Steroid Signaling, NISS), the receptor functioning in this case as an estrogen-dependent transcription factor (or as a coregulator of other transcription factors).…”
Section: The Regulatory Function Of Cam Concerns the Nuclear Form Of Erαmentioning
confidence: 99%
“…One of these is G protein-coupled estrogen receptor 1 (Gper1), which upon binding to estrogens stimulates adenylyl cyclase and EGFR transactivation leading to Ca 2+ mobilization and activation of the mitogen-activated protein kinase Erk1/2 and PI3K/Akt signaling pathways [14,15]. However, it is still controversial that Gper1 is a membrane ER that mediates the non-genomic, rapid effects of estrogens because Pedram et al [16] have shown that E2 fails to activate the rapid multiple pathways in cells that lack classical ERα and ERβ even when Gper1 is present.…”
Section: Cell Culturementioning
confidence: 99%